Analisa Tingkat Pengetahuan dan Perilaku Masyarakat Terhadap Penggunaan Antibiotik di Kelurahan Dawi-Dawi, Kecamatan Pomalaa, Kabupaten Kolaka, Provinsi Sulawesi Tenggara: Analysis Of Community Knowledge and Behavior Level on The Use of Antibiotics Kelurahan Dawi-Dawi, Kecamatan Pomalaa, Kabupaten Kolaka, Southeast Sulawesi Province - Devitha Farah Mahdiyah; Dewi Mayasari; Hadi Kuncoro (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Antibiotics are an effective therapy diseases caused by bacteria so that patients or the public sometimes use them as self-medication drugs. Due to the lack of knowledge and behavior of the community this can lead to cases of antibiotic resistance. The purpose was to determine the level of knowledge and behavior of the community towards the use of antibiotics in Kelurahan Dawi-Dawi, Southeast Sulawesi province. The knowledge and behavior of the community was obtained using a simple descriptive method, cross sectional, with an instrument in the form of a questionnaire that could be distributed to the community to be analyzed regarding the level of knowledge and behavior. This research has involved 196 test respondents. The results showed that the profile of the characteristics of the respondents were mostly female, 35-44 years old, last graduated from high school and worked as a housewife. For the overall results of Kelurahan Dawi-Dawi, Southeast Sulawesi province, having sufficient knowledge 42.9% and sufficient behavior 49.0%. The results of the test of the relationship between knowledge and people's behavior were obtained for the correlation coefficient value using the Spearman formula is Has a moderate correlation of 0.357, a significance of 0.000 with the direction (+).